Qualitative phytochemical screening and GC-MS profiling of Azadirachta excelsa leaf extract - Nurul ‘Izzati Shafie,; Nurdiana Samsulrizal,; Nurfarhana Ahmad Sopian,; Mohamed Ali Rajion,; Goh, Yong Meng; Mohd Mokrish Md. Ajat,; Hafandi Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2015)
Azadirachta excelsa is traditionally used by the locals to treat diabetes mellitus but the active compounds of the leaves have not been identified yet. Hence, the aim of the study was to identify the components of Azadirachta excelsa leaf extract by qualitative phytochemical screening and gas chromatography-mass spectrometry (GC-MS). Five grams of leaf extract were extracted using various solvents for phytochemical screening, while another five grams of ethanolic leaf extract was subjected for GC-MS analysis where the mass spectra of the compounds detected were matched with the National Institute of Standards and Technology (NIST) library. The results showed the presence of flavonoids, condensed tannin, triterpenes and steroids in phytochemical screening tests, while GC-MS analysis revealed the presence of seven major compounds in the ethanolic leaf extract. The major component of A.excelsa ethanolic leaf extract was 9, 12, 15-octadecatrienoic acid (42.34%), followed by pentadecanoic acid, 14-methyl-, methyl ester (28.99%), phytol (10.63%), 9, 12, 15-octadecatrien-1-ol (5.37%), octadecanoic acid, methyl ester (4.36%), 9, 12-octadecadienoic acid, methyl ester (4.24%) and hexadecanoic acid, ethyl ester (4.06%). Therefore, the findings of this study form a basis for the characterization of the compounds and allow researchers to investigate the potential of this plant in treating diabetes mellitus.